Taxonomy- and trait-based responses of chironomid assemblage structure to pollution in selected urban rivers, Eastern Cape, South Africa - Osoh, Miracle Ogagaoghene (Rhodes University, Faculty of Science, Institute for Water Research)
Urbanisation, occasioned by an increasing human population and the proliferation of industries, is a major threat to freshwater resources and has been implicated as a cause of stream water quality deterioration, habitat degradation, and the loss of aquatic biodiversity. Pollution of freshwater systems resulting from urban-related activities severely alters stream ecosystem structure and function. To effectively protect and sustainably manage freshwater resources, it is important to develop biomonitoring tools which are both sensitive to changes in water quality conditions and can provide an understanding of the mechanisms by which urban pollution impacts freshwater ecosystems. In South Africa, the macroinvertebrate-based South African Scoring System version 5 (SASS5) is routinely used for water quality assessment. This tool is developed at the family level of taxonomic resolution, with the exception of a few taxa. This raises the question as to whether a species-level taxonomic approach, complemented with a trait-based approach could add additional value. This question was addressed comparatively by developing and applying a taxonomy- and trait-based approach using the taxonomically and functionally diverse Chironomidae family. Fifteen sites across three urban river systems (Buffalo, Bloukrans and Swartkops River systems) in the Eastern Cape Province of South Africa were purposefully selected for this study. Based on the predominant land use within the catchment of the sites and water quality variables, the study sites were grouped into five site categories. The least-impacted sites (REF) had 78.53% mean forested area, 5.98% mean urban area and 13.49% mean agricultural land. Sites that received diffuse pollution but were upstream from the effluent discharge point of wastewater treatment works (DP) had 59.07% mean forested area, 32.53% mean urban area and 6.20% mean agricultural land. Sites that received point source pollution from wastewater treatment works (PP) had 63.66% mean forested area, 26.26% mean urban area and 7.39% mean agricultural land. Sites further downstream from the wastewater treatment works that received impacts from both point source and diffuse pollution (AG) had 65.95% mean forested area, 18.24% mean urban area and 12.5% mean agricultural land. Sites selected for exploring the potential system recovery of the study rivers (RECV) had 77.21% mean forested area, 9.12% mean urban area and 10.7% mean agricultural land. Macroinvertebrates and physicochemical variables were sampled at sites in the Bloukrans and Buffalo rivers over four sampling events (spring, summer, winter, and autumn) between November 2021 and June 2022 using the SASS5 protocol. Historical chironomid and physicochemical data from the Swartkops River collected between 2009 and 2012 were also used in this study. The SASS5 family-level biotic index classified the water quality condition at the least impacted site (REF) of the Swartkops River as minimally impaired 80% of the time, compared to the chironomid-based multimetric index (CUMMI), which indicated that the water quality condition at this site was near-natural 50% of the time. The chironomid-based multimetric index and the SASS5 were divergent in their classification of water quality conditions at the DP and AG sites but were 100% in agreement regarding water quality conditions at the PP site as critically/severely modified. The SASS5 scores classified the water quality condition at the AG site as critically/severely modified 100% of the time, whereas the CUMMI index classified the water quality condition at this site as critically/severely modified 90% of the time but moderately modified 10% of the time. The results indicate that species-level and family-level indices tend to be in agreement for heavily impacted sites, but the same was not true for least or moderately impacted sites. Traits such as the possession of tracheal gills, very large body size, burrowing, whole-body undulation, construction of rigid tubes, possession of three tracheae, completion of lifecycle in more than one year, production of more than 1000 eggs per egg mass, preferences for fine detritus, and bivoltinism were deemed tolerant of urban pollution. Traits such as cuticular respiration, medium body size, predator feeding mode, completion of lifecycle within one year, and a preference for stone biotope were deemed sensitive to urban pollution. An approach was developed to classify chironomids into those that are potentially vulnerable and those that are resilient to urban pollution. The abundances of vulnerable species correlated positively with increasing dissolved oxygen and negatively with increasing turbidity, electrical conductivity, nitrite-nitrogen, ammonium-nitrogen, and orthophosphate-phosphorus. The relative abundance of the highly vulnerable species and that of the highly tolerant species responded significantly to urban pollution and differentiated between the site categories. The relative abundance of the highly vulnerable species was significantly different between the DP and PP site categories. The richness of vulnerable and highly vulnerable species was significantly different between the REF sites and the impacted site categories (DP, PP, and AG). These results indicated that the developed approach successfully predicted chironomid responses to urban pollution. Overall, the study makes important contributions to the field of freshwater biomonitoring. First, the study highlighted that species-level identification is necessary to differentiate sites which may be considered moderately impacted. Both family and species-level tools were sensitive to water quality conditions for least impacted and highly impacted sites, but the differences between the family-level and species-level indices were pronounced for sites considered moderately impacted. Second, a trait-based approach provided a mechanism for developing predictive tools, and in the case of this study, the potential resilience or vulnerability of chironomids was reliably predicted.
Keywords: Environmental monitoring; Chironomidae; Water quality; Urbanization; Aquatic insects; Aquatic ecology; Urban pollution